2013
DOI: 10.4172/2161-0509.s12-001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diversity and Nutritional Status of Urban Primary School Children from Iran and India

Abstract: Introduction: Nutritional status of children is influenced by diet. Better dietary diversity helps ensure adequate intake of essential nutrients especially for growing school going children. The aim of this study was to assess the effect of dietary scores and nutritional status of urban Iranian and Indian school children. Methods: The present study examined dietary diversity, weight-forage (WA) and height-forage (HA) and weightfor-height weight-forage z-scores and nutritional status of 4570 children aged 6-9 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
2
22
0
3
Order By: Relevance
“…Low child DDS (≤4) in the current study was significantly associated with stunting status [AOR (95% CI) = 2.3 (1.2, 4.7)] suggesting that a diet habitually low in micronutrients may have contributed to stunting in the current study. DDS is a recommended qualitative indicator of micronutrient adequacy of a diet [27,45] and has been shown to predict growth of children in other studies [14,46,47]. On the other hand, DDS was not independently associated with wasting status; a similar finding to previous studies that reported DDS was associated with stunting, but not with wasting [14,46,47].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Low child DDS (≤4) in the current study was significantly associated with stunting status [AOR (95% CI) = 2.3 (1.2, 4.7)] suggesting that a diet habitually low in micronutrients may have contributed to stunting in the current study. DDS is a recommended qualitative indicator of micronutrient adequacy of a diet [27,45] and has been shown to predict growth of children in other studies [14,46,47]. On the other hand, DDS was not independently associated with wasting status; a similar finding to previous studies that reported DDS was associated with stunting, but not with wasting [14,46,47].…”
Section: Discussionsupporting
confidence: 79%
“…DDS is a recommended qualitative indicator of micronutrient adequacy of a diet [27,45] and has been shown to predict growth of children in other studies [14,46,47]. On the other hand, DDS was not independently associated with wasting status; a similar finding to previous studies that reported DDS was associated with stunting, but not with wasting [14,46,47]. DDS may not necessarily reflect variation in energy intake of children as a child may have optimal energy intake from a monotonous starch based diet with low diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research has been done on the methods used to measure diet quality, resulting in the development of several indices (Savy et al, 2005). A 24-hour diet recall method was recommended by the FAO (FAO, 2013), while Hooshmand and Udipi (2013) used food frequency to measure dietary diversity. Food frequency helps to assess the habitual dietary pattern, which is useful to understand the relationship between diet and chronic diseases (FAO, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…the frequency of consumption (daily, twice or three times a week, once a week, fortnightly and occasionally) by a household for the different food groups for a reference period of the preceding one month. The following consumption scores were given: daily: 7; twice or three times a week: 3; once a week: 1; fortnightly: 0.5; monthly: 0.25; and occasionally: 0 (following Hooshmand & Udipi, 2013). The scores were added to obtain the food diversity score for the household.…”
Section: Dietary Diversitymentioning
confidence: 99%